2013
DOI: 10.1155/2013/609745
|View full text |Cite
|
Sign up to set email alerts
|

Oat Protects against Diabetic Nephropathy in Rats via Attenuating Advanced Glycation End Products and Nuclear Factor Kappa B

Abstract: Oat, a rich source of soluble fiber, was considered to have a possible preventive effect on the progression of diabetic nephropathy. The present study aimed to assess this preventive activity in a rat model of diabetic nephropathy. Adult Wister rats were injected by streptozotocin (65 mg/kg). Animals were fed with normal diet or with a diet containing 20% oat (W/W) for 21 weeks. At the end of 21 weeks, all the kidney tissues were collected for various examinations. Our results suggested that oat could decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Oats are a source of several natural antioxidants [260]. Oat downregulates the TGF-β1 and receptors for AGE expression at mRNA levels and it can suppress DN in rats and may slow down renal fibrosis by the disruption of the detrimental receptors for AGE-NFκB axis [261]. After 12 weeks of diabetes in rats, oat treatment reduced BGL, HbA1c, and OS markers, and normalized NFκB activation and TNF-α expression.…”
Section: Oatsmentioning
confidence: 99%
“…Oats are a source of several natural antioxidants [260]. Oat downregulates the TGF-β1 and receptors for AGE expression at mRNA levels and it can suppress DN in rats and may slow down renal fibrosis by the disruption of the detrimental receptors for AGE-NFκB axis [261]. After 12 weeks of diabetes in rats, oat treatment reduced BGL, HbA1c, and OS markers, and normalized NFκB activation and TNF-α expression.…”
Section: Oatsmentioning
confidence: 99%
“…Although primitive, increasing dietary fiber content attenuates the increase in AGEs and slows the progression of CKD. For instance, consumption of a high-fiber diet, such as oats, in rats slowed the progression of diabetic nephropathy with a concurrent reduction in RAGE and NF-κB levels [51]. Sevelamer carbonate, a nonabsorbed phosphate-binding polymer, is frequently used in CKD patients to decrease serum phosphate levels [52,53].…”
Section: Limiting the Exogenous Sources Of Advanced Glycation End Promentioning
confidence: 99%
“…In hyperglycemia, various mechanisms generate free radicals, leading to the oxidation of lipids, proteins, and DNA, resulting in a significant state of oxidative stress [ 69 ]. The increase in free radicals reduces the production of biological antioxidative enzymes such as CAT, SOD, and GSH [ 70 ], making the tissues more vulnerable to oxidative stress [ 71 ]. The intervention of all fermented oat extracts in the present study recovered the altered activity of antioxidant enzymes in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we found that HFOE2 was more effective than the other subjected extracts and even more effective than Metformin treatment at preventing oxidative stress. These effects are strongly related to a decrease in lipid peroxidation [ 71 ], which could be attributed to the combination of the antioxidant activities of oats, honey, and L. plantarum metabolites [ 58 , 66 , 71 ]. Therefore, our results support the hypothesis that a good-quality cereal-based symbiotic product possesses potent antidiabetic activities with antioxidative stress potential.…”
Section: Discussionmentioning
confidence: 99%